The Evaluation of a Risk Degree for the Process of a Brown Coal Spontaneous Ignition on Dumps with Using of Modern Numeric Methods - Klouda Petr; Moni Vlastimil; Řehoř Michal; Blata Jan; Helebrant František (Management Systems in Production Engineering, 2018)
The article is a summary of information about evaluation of a risk degree for a brown coal spontaneous ignition which is realized on the base of a database analysis of information about the development of stative quantities and desorbated gases in the stored bodies of the brown coal. The data were gained from the long term complex measurements which were realized at chosen companies during the coal mining in the previous parts of the project. In the last part of the project, we examined results of temperature models from thermographs with results of gasses and coal samples from the mines. Then, the influence of atmospheric conditions (insolation, water downfall, changes of barometric pressure etc.), the influence of coal mass degradation, the influence of physical and chemical factors, and the influence of other defective factors on the process of the coal spontaneous ignition. The gasmetry was assess with gas in-situ samples and laboratory gas models of indicative gasses for the spontaneous ignition, which were taken from the method of the thermic oxidation with the aim of the correlation finding for an epicentre of temperature within the spontaneous ignition.